Adaptabilidade e estabilidade fenotípica de genótipos de soja pelos métodos de Toler e Centróide - Hamawaki, Raphael Lemes (2014)
Brazil is the second largest global producer and the major global exporter of soybeans. The total foreign exchange income from the soybean complex was US$ 26.1 billion in the 2012/2013 growing season. This result comes from the fast expansion of this oilseed crop in different regions of the country. Due to the diversity of climatic and soil conditions in Brazil the genotype x environment interaction component is important in the improvement of genotypes for higher yields, The accurate estimation of the magnitude of this component is of utmost importance to the breeder as it allows selecting genotypes that fit in a certain growing region, and in a similar way selecting growing conditions for the maximum yield of a certain genotype. The purpose of this study was to evaluate the performance of 14 semi-late and late soybean genotypes, coming from the Soybean Breeding Program of the Federal University of Uberlandia, in their adaptive capacity and yield stability in three locations (Porangatu - GO, Porto Alegre do Norte - MT and Uberaba - MG) in the 2005/2006 and 2007/2008 growing seasons. For the adaptability and phenotypic stability analysis were used the methodology proposed by Toler (1990) and the Centroid method proposed by Rocha et al. (2005) and modified by Nascimento et al. (2009). A variance analysis was performed for each environment followed by a joint analysis where a significant effect for the genotype x location x year interaction component was detected. In the Centroid method analysis the genotype of higher average yield (UFU-002) was also the only one included in the ideotype VI of medium adaptability to favorable environments; by this same method 78.5% of the genotypes were included in the ideotype V of medium general adaptability. The analysis using Toler\'s (1990) method identified five genotypes with a divided pattern of response, being UFU-001, UFU-003, UFU-0010 and UFU-0011 classified in Group A with a convex pattern (doubly desirable), whereas genotypes UFU-008 and UFU-0013 were classified in Group E with a concave pattern (doubly undesirable). The genotype UFU-006 was classified as group B with specific adaptability to favorable environments; on the other hand genotype-UFU 0012 was classified as group D with specific adaptability to unfavorable environments. The graphic analysis using Toler\'s method was more conclusive, with better characterization of the genotypes behavior in favorable and unfavorable environments. The genotype UFU-008 was the only one to show low adaptive capacity to the evaluated environments by both methodologies. The genotypes UFU-001, UFU-002, UFU-006, UFU-0010 and UFU-0011 are the most recommended ones for the evaluated growing region, with high yield potential, specifically in high quality environments.